Hubungan Pengetahuan dan Sikap Kesehatan Gigi Mulut dengan Angka Karies pada Masyarakat Perdesaan (Kajian pada Desa Karangtengah, Kecamatan Baturraden, Kabupaten Banyumas) (Berita Kedokteran Masyarakat (BKM), 2020)
Introduction: The results of Riskesdas (Baseline Health Research) by Indonesian Ministry of Health in 2018 showed that the caries rate in rural areas was higher than in urban areas. However, the number of villagers receiving dental and oral health care was lower in comparison to urban communities. Karangtengah Village was located in the Baturraden District, Banyumas Regency which is a rural area. Purpose: This study aimed to determine the correlation of knowledge and attitude about oral health with caries rate in Karangtengah Village. Method:The study was an observational analytical research. Subjects were chosen using purposive sampling technique. Total subjects were 388 residents. The knowledge and affective data were collected using questionnaire and the caries rate was scored using DMF-T. Data was analyzed using Pearson correlation test (SPSS 22). Results: The results showed that the oral health knowledge and attitude of the majority of Karangtengah Village residents were in moderate category (48.7% and 66.8% respectively), while the average DMF-T score was 13.12 (very high). The statistical analysis showed no significant correlation between knowledge and DMF-T score as well as between attitude of oral health and DMF-T score (p>0.5). Conclusion:The moderate category of oral health knowledge and attitude in rural may have not applied as oral health behaviors therefore contribute to high dental caries rates.